Cardiovascular disease and thinning of retinal nerve fiber layer in a multi-ethnic Asian population: the Singapore epidemiology of eye diseases study - Majithia, Shivani; Quek, Debra Q. Y.; Chee, Miao Li; Lim, Zhi Wei; Nusinovici, Simon; Soh, Zhi-Da; Thakur, Sahil; Rim, Tyler Hyungtaek; Sabanayagam, Charumathi; Cheng, Ching-Yu; Tham, Yih-Chung (Frontiers in Medicine, 2023)
Introduction: Our study aimed to examine the relationship between cardiovascular diseases (CVD) with peripapillary retinal fibre layer (RNFL) and macular ganglion cell-inner plexiform layer (GCIPL) thickness profiles in a large multi-ethnic Asian population study. Methods: 6,024 Asian subjects were analysed in this study. All participants underwent standardised examinations, including spectral domain OCT imaging (Cirrus HD-OCT; Carl Zeiss Meditec). In total, 9,188 eyes were included for peripapillary RNFL analysis (2,417 Malays; 3,240 Indians; 3,531 Chinese), and 9,270 eyes (2,449 Malays, 3,271 Indians, 3,550 Chinese) for GCIPL analysis. History of CVD was defined as a self-reported clinical history of stroke, myocardial infarction, or angina. Multivariable linear regression models with generalized estimating equations were performed, adjusting for age, gender, ethnicity, diabetes, hypertension, hyperlipidaemia, chronic kidney disease, body mass index, current smoking status, and intraocular pressure. Results: We observed a significant association between CVD history and thinner average RNFL (β=-1.63; 95% CI, -2.70 to -0.56; P=0.003). This association was consistent for superior (β =-1.79, 95% CI, -3.48 to -0.10; P=0.038) and inferior RNFL quadrant (β=-2.14, 95% CI, -3.96 to -0.32; P=0.021). Of the CVD types, myocardial infarction particularly showed significant association with average (β=-1.75, 95% CI, -3.08 to -0.42; P=0.010), superior (β=-2.22, 95% CI, -4.36 to -0.09; P=0.041) and inferior (β= -2.42, 95% CI, -4.64 to -0.20; P=0.033) RNFL thinning. Among ethnic groups, the association between CVD and average RNFL was particularly prominent in Indian eyes (β=-1.92, 95% CI, -3.52 to -0.33; P=0.018). CVD was not significantly associated with average GCIPL thickness, albeit a consistent negative direction of association was observed (β= -0.22, 95% CI, -1.15 to 0.71; P=0.641). Discussion: In this large multi-ethnic Asian population study, we observed significant association between CVD history and RNFL thinning. This finding further validates the impact of impaired systemic circulation on RNFL thickness.